2015
DOI: 10.1021/acsnano.5b05498
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Time Window for Dynamic Nanowire Cell Penetration Processes

Abstract: Nanowire (NW) arrays offer opportunities for parallel, nondestructive intracellular access for biomolecule delivery, intracellular recording, and sensing. Spontaneous cell membrane penetration by vertical nanowires is essential for these applications, yet the time- and geometry-dependent penetration process is still poorly understood. In this work, the dynamic NW-cell interface during cell spreading was examined through experimental cell penetration measurements combined with two mechanical models based on sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 71 publications
3
86
1
Order By: Relevance
“…2 to estimate S contact leads to a critical stress of~8 kPa, it is probably more accurate to estimate the contact area as that of a spherical cap, S contact2 pR 2 , leading to a larger stress of~50 kPa. In another study using nanoneedle geometries, Xie et al (46,47) investigated the penetration of nanowires fixed to a substrate into cells that adhere to this substrate. They used a cell membrane rupture criterion based on activation energy theory and leading to a critical membrane tension to be reached before rupture (42,44).…”
Section: Discussionmentioning
confidence: 99%
“…2 to estimate S contact leads to a critical stress of~8 kPa, it is probably more accurate to estimate the contact area as that of a spherical cap, S contact2 pR 2 , leading to a larger stress of~50 kPa. In another study using nanoneedle geometries, Xie et al (46,47) investigated the penetration of nanowires fixed to a substrate into cells that adhere to this substrate. They used a cell membrane rupture criterion based on activation energy theory and leading to a critical membrane tension to be reached before rupture (42,44).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the literature, interactions are variously described as penetrating, piercing, perturbing, impaling, indenting, and mechanically disrupting the cell membrane, which reflects in part the lack of consensus over what is happening. In particular, many reports question whether the cell membrane is spontaneously penetrated by nanostructures, and this topic has been presented as a source of contention within the field. In this context, spontaneous penetration refers to a high‐aspect‐ratio nanostructure piercing the membrane of a cell that has been seeded onto a surface (with minimal applied external force).…”
Section: Understanding the Cell–nanostructure Interfacementioning
confidence: 99%
“…Despite successful delivery of a broad variety of biomolecules into diverse cell types, the exact mechanism of whether and how the NW arrays can mechanically pierce cellular membranes and/or the nucleus is still not well understood, and has been the subject of an ongoing debate for almost a decade . Various reports have demonstrated that NW‐mediated intracellular delivery often relies on mechanical penetration, which can be maximized by manipulating a combination of key parameters, such as application of external force, interfacing approaches,13f,25 cellular adhesion force,9a,26 NW geometry (density, length, and diameter),17b,27 surface functionalization, and interfacing time . For example, effective delivery of biomolecules (plasmid DNAs, siRNAs, and proteins) into smaller immune cells that grow in suspension requires the use of longer (2−3 µm), sharper (diameter < 150 nm), and denser (0.3−1.0 NWs µm −2 ) NWs, whereas slightly shorter and less dense NWs are more suitable for larger adherent cells 17b.…”
Section: Introductionmentioning
confidence: 99%
“…For example, effective delivery of biomolecules (plasmid DNAs, siRNAs, and proteins) into smaller immune cells that grow in suspension requires the use of longer (2−3 µm), sharper (diameter < 150 nm), and denser (0.3−1.0 NWs µm −2 ) NWs, whereas slightly shorter and less dense NWs are more suitable for larger adherent cells 17b. Arguing against NW‐mediated direct penetration, some work has posited that the majority of NWs fail to gain a stable access to the cell interior spontaneously,10a,29,30 and others have suggested that endocytosis could be one of the prevalent mechanisms behind NW‐mediated intracellular delivery 23a. In particular, recent studies have shown evidence that vertical nanostructures induce well‐defined membrane curvatures, stimulating clathrin‐mediated endocytosis (CME) and caveolae‐mediated endocytosis (CavME) 23a,31.…”
Section: Introductionmentioning
confidence: 99%